Harmonização e complementaridade entre as políticas para a agricultura do Brasil e da União Europeia - Colle, Célio Alberto (2017)
The EU's Common Agricultural Policy (CAP), created in the late 1950s, underwent several changes and incorporated environmental issues over time; it was eventually consolidated in the Agenda 2000. The EU has also made progress in defining agriculture; in addition to producing grains and meat, it also produces public goods, and such production is called multifunctional agriculture. Brazil has been showing signs that it intends to incorporate environmental conservation through production support policies, which is a similar path to that already covered by the EU. This direction for harmonization of agricultural and environmental policies is partly guided by global environmental measures. One of these agreements is the United Nations Framework Convention on Climate Change (UNFCCC), which sets targets for reducing greenhouse gas emissions. Agriculture contributes with some of these emissions and, therefore, programs are being created to mitigate them. In this context, reduction programs and targets for the agricultural sector in Brazil and in the EU are in progress. Thus, the general objective of this thesis is to analyze the harmonization of policies and the complementarity between them by considering two distinct sets of public policies: PRONAF and the ABC Program, in Brazil; LEADER and the TFCs, for the EU. The methodology is guided by building two matrices of analysis: one has three dimensions (productive, environmental and sociocultural), with three parameters each, to verify the harmonization of each one of the policies; the second matrix (also with three parameters and three dimensions) was created to verify the complementarity between the policies, which were analyzed two by two. Based on the description resulting from the application of such matrices, a practical exercise is carried out with the four policies. The analyses indicate high harmonization between the dimensions for PRONAF, TFC and LEADER and low harmonization for the ABC Program. The latter’s low harmonization is due to the absence of relations between the parameters of the sociocultural dimension. By analyzing the complementarity, high complementarity between the TFCs and LEADER was evidenced, in which seven of the nine parameters occurred in both policies. By analyzing PRONAF with TFC and PRONAF with LEADER, medium harmonization was observed, with the occurrence of five parameters in both policies. On the other hand, all policies analyzed together with the ABC Program have resulted in low complementarity. This indicates the similarity between the ones with high and medium complementarity and the difference from the ABC Program, indicating that it was created to meet the National Program of Climate Change and that such measures have been little internalized in the other programs. The logic of the methodology proposed can be applied to the analysis and verification of other public policies from the definition of objectives, goals and results, for example.